Using the DLOQ in a Military Context: Culture Trumps Strategy. (May 2013) - Stothard, Christina; Talbot, Steven; Drobnjak, Maya; Fischer, Tiffany
The Problem: The learning organization is a term frequently used to reflect a set of ideas that have been around for some time—that is, successful adaptation to change and uncertainty is more likely to occur through the learning efforts of both individuals, and the organization as a whole. The term, however, has become a common phrase for describing a host of approaches to organizational development and activity occurring within organizations; however little space has been dedicated to the application of learning organization ideas and practices within military institutions. Given the diversity that exists within many large organizations, it is surprising how little attention has been given to the significance of learning in terms of hierarchy and rank within the learning organization discourse. The Solution: Drawing on data collected from 1, 061 respondents, this article compares and contrasts the learning cultures of a selection of headquarters and brigades within the Australian Army, and considers the extent to which their respective learning cultures align with those described as learning organizations. Results suggest that headquarter and brigade elements express similar learning behaviors to those found in learning organizations. However, respective learning cultures differ according to a variety of organizational factors including functional roles, leadership styles, and rank. The Stakeholders: Human resource and organization developers working in military contexts will find this information particularly useful as well as scholars interested in investigating the learning culture.